Aging alters spontaneous and neurotransmitter‐mediated Ca2+ signaling in smooth muscle cells of mouse mesenteric arteries. (15th March 2020) - Boerman, Erika M.; Segal, Steven S.
Abstract: Objective: Aging impairs MA dilation by reducing the ability of sensory nerves to counteract sympathetic vasoconstriction. This study tested whether altered SMC Ca 2+ signals to sympathetic (NE) and sensory (CGRP) neurotransmitters underlie aging‐related deficits in vasodilation. Methods: MAs from young and old mice were pressurized and loaded with Fluo‐4 dye for confocal measurement of SMC Ca 2+ sparks and waves. Endothelial denudation resolved the influence of ECs. SMCs were immunolabeled for RyR isoforms and compared with transcript levels for RyRs and CGRP receptor components. Results: SMCs from young vs old mice exhibited more spontaneous Ca 2+ spark sites with no difference in Ca 2+ waves. NE reduced spark sites and increased waves for both groups; addition of CGRP restored sparks and reduced waves only for young mice. Endothelial denudation attenuated Ca 2+ responses to CGRP for young but not old mice, which were already attenuated, suggesting a diminished role for ECs with aging. CGRP receptor expression was similar between ages with increased serum CGRP in old mice, where RyR1 expression was replaced by RyR3. Conclusion: With aging, we suggest that altered RyR expression in SMCs contributes to impaired ability of sensory neurotransmission to restore Ca 2+ signaling underlying vasomotor control during sympathetic activation.